Overcoming Instructor-Originated Math Anxiety in Philosophy Students: A Consideration of Proven Techniques for Students Taking Formal Logic. - Macpherson, Brian (Metaphilosophy, 2016)
Every university student has his or her nemesis. Biology and social science students anticipate with great apprehension their required statistics course, while many philosophy students live in fear of formal logic. Math anxiety is the common thread uniting all of them. This article argues that since formal logic is an algebra requiring similar kinds of symbol-manipulation skills needed to succeed in a basic mathematics course, then if logic students have math anxiety, this can impede their progress. Further, it argues that math anxiety is primarily caused by and exacerbated by poor instruction. Formal logic instructors who employ effective instructional techniques for reducing it can help their students overcome math anxiety to foster learning. Methods of instruction leading to anxiety reduction and evidence supporting their efficacy are discussed, including co-operative learning, the mastery goal approach, and self-paced learning. None of these methods holds back more advanced students.